An engineered thermal-shift screen reveals specific lipid preferences of eukaryotic and prokaryotic membrane proteins. Issue 1 (December 2018) - Nji, Emmanuel; Chatzikyriakidou, Yurie; Landreh, Michael; Drew, David
Abstract Membrane bilayers are made up of a myriad of different lipids that regulate the functional activity, stability, and oligomerization of many membrane proteins. Despite their importance, screening the structural and functional impact of lipid–protein interactions to identify specific lipid requirements remains a major challenge. Here, we use the FSEC-TS assay to show cardiolipin-dependent stabilization of the dimeric sodium/proton antiporter NhaA, demonstrating its ability to detect specific protein-lipid interactions. Based on the principle of FSEC-TS, we then engineer a simple thermal-shift assay (GFP-TS), which facilitates the high-throughput screening of lipid- and ligand- interactions with membrane proteins. By comparing the thermostability of medically relevant eukaryotic membrane proteins and a selection of bacterial counterparts, we reveal that eukaryotic proteins appear to have evolved to be more dependent to the presence of specific lipids. Membrane bilayers are made up of a myriad of different lipids that affect membrane proteins, but identifying those specific lipid requirements remains a challenge. Here authors present an engineered thermal-shift screen which reveals specific lipid preferences of eukaryotic and prokaryotic membrane proteins.